Pengolahan Limbah Cair Laundry Menggunakan Aluminium Sulfat dari Fly Ash dengan Metode Koagulasi - Flokulasi - Adelita Sidabutar; Utami, Noni Esti; Srie Muljani; Caecillia Pujiastuti; Sani (Jurnal Serambi Engineering, 2026)
Laundry wastewater poses thousand risk for the environment and microbes due to its detergent content that remain the same from washing process using detergent and any other substance. These detergents can trigger various issues such as eutrophication in rivers and health problems caused by their chemical components. Therefore, further treatment is necessary to ensure the wastewater meets quality standards and is safe for discharge into the environment. Fly ash, which contains a high concentration of aluminum, can be utilized through a synthesis process to produce alum. This alum is then applied in coagulation–flocculation processes to reduce pollutants in laundry wastewater, such as BOD, COD, and TSS. This study aims to determine the optimal dosage and contact time of fly ash alum in treating wastewater to meet quality standards, using dosage variations of 30, 40, 50, 60, and 70 mL and flocculation times of 45, 55, 65, 75, and 85 minutes. The results of the treatment using fly ash alum are then compared with those using commercial alum to identify the most effective treatment. Consequently, the synthesis and treatment process not only contribute to wastewater management but also offer an alternative solution for coagulant and flocculant materials.